GAMBARAN PENGELOLAAN LABORATORIUM IPA TERPADU (BIOLOGI) DI SMP N SE KECAMATAN PAGARAN TAPAH DARUSSALAM TAHUN PEMBELAJARAN 2015/2016 - Mukaromah, luluk Hidayatul (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
This purpose of the research known image management laboratory IPA Terpadu (Biology) of SMP Negeri subdistrict Pagaran Tapah Darussalam at management laboratory grade academic year 2015/2016. The sampel of the reseach was 8 teachers IPA Terpadu (biology) of SMP Negeri subdistrict Pagaran Tapah Darussalam that taken in âtotal samplingâ. Technique intake of data done by using enquette. Data were analyzed using descriptive. The Result of research indicate that: 1) management laboratory work 67,69%, 2) executionÂ  laboratory work 70,03%,3) situation laboratory work 73,49%, and 4) save instrument and material laboratory work 75,44%. Amount of mean percentage of management laboratory of study IPA Terpadu (Biology) work 71,72% have been applied better.